Impairment of Nuclear Pores in Bovine Herpesvirus 1-Infected MDBK Cells - Wild, Peter (American Society for Microbiology, 2005)
Herpesvirus capsids originating in the nucleus overcome the nucleocytoplasmic barrier by budding at the inner nuclear membrane. The fate of the resulting virions is still under debate. The fact that capsids approach Golgi membranes from the cytoplasmic side led to the theory of fusion between the viral envelope and the outer nuclear membrane, resulting in the release of capsids into the cytoplasm. We recently discovered a continuum from the perinuclear space to the Golgi complex implying (i) intracisternal viral transportation from the perinuclear space directly into Golgi cisternae and (ii) the existence of an alternative pathway of capsids from the nucleus to the cytoplasm. Here, we analyzed the nuclear surface by high-resolution microscopy. Confocal microscopy of MDBK cells infected with recombinant bovine herpesvirus 1 expressing green fluorescent protein fused to VP26 (a minor capsid protein) revealed distortions of the nuclear surface in the course of viral multiplication. High-resolution scanning and transmission electron microscopy proved the distortions to be related to enlargement of nuclear pores through which nuclear content including capsids protrudes into the cytoplasm, suggesting that capsids use impaired nuclear pores as gateways to gain access to the cytoplasmic matrix. Close examination of Golgi membranes, rough endoplasmic reticulum, and outer nuclear membrane yielded capsid-membrane interaction of high identity to the budding process at the inner nuclear membrane. These observations signify the ability of capsids to induce budding at any cell membrane, provided the fusion machinery is present and/or budding is not suppressed by viral proteins.